Relationship between the Characteristics and Knowledge of Birth Control Pill Acceptors and Adherence to Taking Birth Control Pills in the Work Area UPT. Barong Tongkok Health Center - Ekalista; Dini Indo Virawati; Satriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between the characteristics and knowledge of birth control pill acceptors with consumption compliance in the Barong Tongkok Health Center area. This type of research is analytic observational with a cross sectional approach. The population in this study were all birth control pill acceptors domiciled in the working area of ​​the Barong Tongkok health center, a total of 297 people. Sampling in this study used a proportional random sampling technique and obtained as many as 93 respondents. Data collection was carried out by interviewing using a questionnaire. The data analysis technique uses the chi square test to determine the relationship between variables. The results of the hypothesis test are that there is a relationship between the characteristics of the respondents, namely age (p-value = 0.000), education (p-value = 0.000), and occupation (p-value = 0.021) with the respondents' compliance in taking birth control pills. There is also a relationship between knowledge and respondents' adherence to taking birth control pills with a p-value = 0.000 (<0.05).